2015
DOI: 10.7326/m14-2062
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin for Women With Unexplained Recurrent Pregnancy Loss

Abstract: Pfizer Pharma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 35 publications
0
60
0
1
Order By: Relevance
“…They concluded that enoxaparin (40 mg once daily) did not improve the chance of a live birth in nonthrombophilic women with unexplained RPL. [14] In another similar multicentre, randomised controlled trial, Schleussner et al [15] determined whether LMWH increases live birth rates in women with unexplained RPL. They enrolled 449 women, with at least 2 early or 1 late miscarriages, at 5 -8 weeks' gestation after confirmation of a viable pregnancy by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that enoxaparin (40 mg once daily) did not improve the chance of a live birth in nonthrombophilic women with unexplained RPL. [14] In another similar multicentre, randomised controlled trial, Schleussner et al [15] determined whether LMWH increases live birth rates in women with unexplained RPL. They enrolled 449 women, with at least 2 early or 1 late miscarriages, at 5 -8 weeks' gestation after confirmation of a viable pregnancy by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some advocated anti-coagulation therapy (such as aspirin or low-molecular-weight-heparin) is effective in improving the pregnancy outcome in women suffered from anti-phospholipid antibody syndrome and RPL but the results were inconsistent among different trials [6, 1921]. Most of the recently conducted randomized trials failed to show significant benefit of anti-coagulation therapy (either aspirin or low molecular weight heparin alone or if both were combined) to improve the livebirth rates in women with RPL [6, 7, 15]. However, these well-conducted trials actually did not well characterize the underlying possible causative factors in their study subjects, the subgroups due to different etiologies were pooled and no specific analyses were conducted separately on each subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous studies, the most common heritable thrombophilias in the thromboembolic patients in Taiwan are protein S and protein C deficiencies [13, 14]. Meanwhile, the selection criteria and treatment protocol varied across different studies and thus we should be cautious when reading reviews based upon meta-analysis [3–5, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, its prescription has been increasing more and more since the mid-90s and has been shown to be safe for both mother and foetus, in spite of the passage through placenta. In women suffering from early pregnancy loss, it has been shown to be not efficacious [69][70][71][72]. The EAGer doubleblind, placebo-controlled randomised controlled trial (RCT) recently suggested that also preconception-initiated low-dose aspirin did not significantly improve the likelihood of delivering a live born child in 1078 women with one to two previous pregnancy losses.…”
Section: Interventions In Gvcsmentioning
confidence: 99%